2018
DOI: 10.1001/jamainternmed.2018.0116
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vaginal Estradiol or Vaginal Moisturizer vs Placebo for Treating Postmenopausal Vulvovaginal Symptoms

Abstract: IMPORTANCE Nearly half of postmenopausal women report bothersome vulvovaginal symptoms, but few data support the efficacy of 2 commonly recommended treatments. OBJECTIVE To compare the efficacy of a low-dose vaginal estradiol tablet and a vaginal moisturizer, each vs placebo, for treatment of moderate-to-severe postmenopausal vulvovaginal symptoms. DESIGN, SETTING, AND PARTICIPANTS This 12-week multicenter randomized clinical trial enrolled postmenopausal women with moderate to severe symptoms of vulvovaginal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 51 publications
7
121
0
2
Order By: Relevance
“…dyspareunia) as required by the FDA, but rather evaluated many different symptoms as a single entity. Nonetheless, the MsFLASH trial found significantly greater improvement in total Menopause-specific Quality of Life Questionnaire scores with the vaginal E2 tablets compared with the placebo gel 16 , and objective findings (vaginal pH and vaginal maturation index) as well as patient satisfaction favored the vaginal E2 tablets versus the placebo gel 14 . Therefore, these results are limited in scope, and clinicians should not disregard the large body of evidence showing that low-dose vaginal estrogen can be useful in the management of GSM.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…dyspareunia) as required by the FDA, but rather evaluated many different symptoms as a single entity. Nonetheless, the MsFLASH trial found significantly greater improvement in total Menopause-specific Quality of Life Questionnaire scores with the vaginal E2 tablets compared with the placebo gel 16 , and objective findings (vaginal pH and vaginal maturation index) as well as patient satisfaction favored the vaginal E2 tablets versus the placebo gel 14 . Therefore, these results are limited in scope, and clinicians should not disregard the large body of evidence showing that low-dose vaginal estrogen can be useful in the management of GSM.…”
Section: Discussionmentioning
confidence: 97%
“…While data from the 12-week GSM trial from the Menopause Strategies: Finding Lasting Answers for Symptoms and Health (MsFLASH) research group suggest that prescribing vaginal 10-mg E2 tablets and over-the-counter vaginal moisturizer does not provide additional benefit over a placebo vaginal tablet and gel in reducing postmenopausal VVA symptoms 14 , the trial had several limitations. As noted by Pinkerton et al 15 , the trial had a small sample size (n ¼ 302); used a non-conventional placebo gel, which might have contributed to the high placebo response; and did not evaluate a specific MBS (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the beneficial effects of vaginal moisturizers are mostly due to adhesive and buffering capacities leading to tissue water retention and vaginal pH reduction. 21 Polycarbophil based moisturizers are as effective as vaginal oestrogen therapy in reducing postmenopausal VVA symptoms 22,23 but not in improving sexual function and menopause-related quality of life. 24 Low dose local oestrogens, in the form of cream, tablet, or ring are all effective for VVA symptoms, with a minimal systemic absorption.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…A systematic review, published in 2014, concluded that all commercially available vaginal estrogens effectively relieve common vulvovaginal atrophy-related complaints and have additional utility in patients with urinary urgency, frequency or nocturia, stress urinary incontinence (SUI) and UUI, and recurrent UTIs [2]. However, a recent large RCT concluded that neither the vaginal estradiol tablet nor the over-the-counter vaginal moisturizer provided additional benefit over placebo in reducing postmenopausal VVS [21].…”
Section: Local Estrogen In the Treatment Of Vvsmentioning
confidence: 99%